2021
DOI: 10.1111/cns.13733
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale whole‐exome sequencing association study identifies FOXH1 gene and sphingolipid metabolism pathway influencing major depressive disorder

Abstract: In the present study, we performed an exome‐wide investigation of the burden of rare disease‐causing variants for major depressive disorder (MDD) using 16,702 samples from UK biobank. Gene‐based association analysis and candidate gene prioritization analysis indicated that FOXH1 have significant association with MDD. In addition, sphingolipid metabolism pathway was found to be less enriched with rare disease‐causing variants in the MDD group, suggesting that this gene set may be involved in the pathophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Advancement in NGS technology can help identify rare variants [ 18 ]. Previous studies have conducted gene-based analyses of rare damaging variants to identify genes related to MDD using the UK Biobank exome dataset [ 19 , 20 ]. Zhou et al revealed that genes based on rare variants, including FOXO1 , MAPK10 , DLGAP3 , ARID5B , ASXL2 , and MED13 , were significantly associated with MDD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancement in NGS technology can help identify rare variants [ 18 ]. Previous studies have conducted gene-based analyses of rare damaging variants to identify genes related to MDD using the UK Biobank exome dataset [ 19 , 20 ]. Zhou et al revealed that genes based on rare variants, including FOXO1 , MAPK10 , DLGAP3 , ARID5B , ASXL2 , and MED13 , were significantly associated with MDD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have conducted gene-based analyses of rare damaging variants to identify genes related to MDD using the UK Biobank exome dataset [ 19 , 20 ]. Zhou et al revealed that genes based on rare variants, including FOXO1 , MAPK10 , DLGAP3 , ARID5B , ASXL2 , and MED13 , were significantly associated with MDD [ 19 ]. Cheng et al performed a gene-based burden test to identify OR8B4 , TRAPPC11 , SBK3 , and TNRC6B between patients with MDD with high polygenic risk scores (PRS) and those with low PRS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous genome-wide association studies (GWAS) have identified common variations related to MDD. However, the estimated heritability of these common genetic mutations ranges from only 9 to 10% ( 4 ). Thus, researchers have shifted their attention to other undiscovered heritability, such as rare gene variations (MAF < 0.5%) and copy number variations (CNVs).…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified 1,985 variations in 479 MDD-related genes using different approaches and databases, reporting 14 gene mutations that differed between patients with MDD and the general South Asian population ( 6 ). A recent study that utilized 16,702 samples from the UK Biobank also highlighted the FOXH1 gene and sphingolipid metabolism pathways as the most significant pathogenic genes for MDD ( 4 ). Despite several advances in understanding the genetic mutations underlying MDD, studies are still scarce and have limitations such as small sample sizes and large numbers of Europeans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have conducted gene-based analyses of rare damaging variants to identify genes related to MDD using the UK Biobank exome dataset [9,10]. Zhou et al revealed that genes based on rare variants, including FOXO1, MAPK10, DLGAP3, ARID5B, ASXL2, and MED13, were signi cantly associated with MDD [9]. Cheng et al performed a gene-based burden test to identify OR8B4, TRAPPC11, SBK3, and TNRC6B between patients with MDD with high polygenic risk scores (PRS) and those with low PRS [10].…”
Section: Introductionmentioning
confidence: 99%